THE ROLE OF THE FOREIGN CURRENCY SELLING WINDOW IN )THE INFLATION RATE IN IRAQ FOR THE PERIOD (2004-2020) - Ahmed Shakir Mahood; Amer Sami Muneer (Scholar Express Journals, 2023)
The research aims to analyze the impact of the foreign currency sale window on inflation rates in Iraq, for the period (2004-2020), as the foreign currency sale window is one of the most important indirect tools used by the monetary authorities in Iraq represented by the Central Bank of Iraq. The important tools that are used in rentier economies, including Iraq, in order to curb inflation by maintaining the general level of prices. The foreign currency sales window is a double-edged sword, as it is used to cover the shortfall in commodity supply through imports, and this represents the positive side of the window. As for the negative side, raising the level of window sales through window transfers or through cash sales contributes to depleting the level of reserves. From the foreign currency represented by (the dollar) through the leakage of hard currencies out of the Iraqi economy, and then the attack on the rights of subsequent generations . The study concluded that the token sale window has an indirect effect on inflation rates, as the increase in window sales contributes to reducing the inflation rate in Iraq
Keywords: foreign currency window; inflation rate; exchange rate